2015
DOI: 10.1038/srep14525
|View full text |Cite
|
Sign up to set email alerts
|

The arsenic hyperaccumulating Pteris vittata expresses two arsenate reductases

Abstract: Enzymatic reduction of arsenate to arsenite is the first known step in arsenate metabolism in all organisms. Although the presence of one mRNA arsenate reductase (PvACR2) has been characterized in gametophytes of P. vittata, no arsenate reductase protein has been directly observed in this arsenic hyperaccumulating fern, yet. In order to assess the possible presence of arsenate reductase in P. vittata, two recombinant proteins, ACR2-His6 and Trx-His6-S-Pv2.5–8 were prepared in Escherichia coli, purified and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Moreover, upregulation of GTR4, AT, AR, MTP10 and PC genes as observed in RT-PCR assay corroborate the reported literature. Based on the DEGs enrichments in the present study and reported literature (Shin et al 2004;Raab et al 2004;Ma et al 2008;Ellis et al 2006;Bienert et al 2008b;Thapa et al 2012;Cesaro et al 2015;Tiwari et al 2016), a possible regulatory network of As uptake, transport and accumulation was put forward in the below-ground tissue of P. vittata (figure 5). The present investigation reports root transcriptome data and provides useful information about the root-specific As-stress- related genes that may pave the way for future functional studies.…”
Section: Root Transcripts Associated With As Stress and Regulatory Nementioning
confidence: 95%
“…Moreover, upregulation of GTR4, AT, AR, MTP10 and PC genes as observed in RT-PCR assay corroborate the reported literature. Based on the DEGs enrichments in the present study and reported literature (Shin et al 2004;Raab et al 2004;Ma et al 2008;Ellis et al 2006;Bienert et al 2008b;Thapa et al 2012;Cesaro et al 2015;Tiwari et al 2016), a possible regulatory network of As uptake, transport and accumulation was put forward in the below-ground tissue of P. vittata (figure 5). The present investigation reports root transcriptome data and provides useful information about the root-specific As-stress- related genes that may pave the way for future functional studies.…”
Section: Root Transcripts Associated With As Stress and Regulatory Nementioning
confidence: 95%
“…Pteris vittata L., a common fern known as ‘Chinese Brake Fern’, is native from China and widespread all over the world (Ma et al 2001 ). It received much attentions in recent years because it was known to be a hyperaccumulator plant of arsenic used in phytoremediation (Cesaro et al 2015 ; Tisarum et al 2015 ; de Oliveira et al 2016 ; Tiwari et al 2016 ). It is also widely used in traditional Chinese medicine for diverse therapeutic applications, such as the treatment of influenza, dysentery, rheumatism, injury and scabies (Xie 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenate reductase assay was performed according to Cesaro et al . 83 . 5 µL of the plant extract was added to a 100 µL of the assay mixture.…”
Section: Methodsmentioning
confidence: 99%